Analysis of six heavy metals in Ortho mineral trioxide aggregate and ProRoot mineral trioxide aggregate by inductively coupled plasma–optical emission spectrometry. (20th March 2012) - Kum, Kee‐Yeon; Zhu, Qiang; Safavi, Kamran; Gu, Yu; Bae, Kwang‐Shik; Chang, Seok Woo
Abstract Ortho mineral trioxide aggregate (MTA) is a mineral aggregate newly developed for perforation repair, root end filling and pulp capping. The aim of this study was to investigate the levels of cadmium (Cd), copper (Cu), iron (Fe), manganese (Mn), nickel (Ni) and zinc (Zn) in Ortho MTA and ProRoot MTA. A total of 0.2 g of each MTA was digested using a mixture of hydrochloric and nitric acids and filtered. Six heavy metals in the resulting filtrates were analyzed by inductively coupled plasma–optical emission spectrometry (n = 5). The results were statistically analyzed using the Mann–Whitney U‐test. The concentrations of Cd, Cu, Fe, Mn, Ni and Zn in Ortho MTA were 0.10, 7.73, 49.51, 2.58, 0.82 and 10.09 p.p.m., respectively. The concentrations of Cd, Cu, Fe, Mn, Ni and Zn in ProRoot MTA were 0.16, 9.38, 1438.11, 74.51, 18.98 and 4.05 p.p.m., respectively. In conclusion, Ortho MTA had lower levels of Cd, Cu, Fe, Mn and Ni than ProRoot MTA.